2008
DOI: 10.1186/1476-072x-7-11
|View full text |Cite
|
Sign up to set email alerts
|

Hydrological modeling of geophysical parameters of arboviral and protozoan disease vectors in Internally Displaced People camps in Gulu, Uganda

Abstract: BackgroundThe aim of this study was to determine if remotely sensed data and Digital Elevation Model (DEM) can test relationships between Culex quinquefasciatus and Anopheles gambiae s.l. larval habitats and environmental parameters within Internally Displaced People (IDP) campgrounds in Gulu, Uganda. A total of 65 georeferenced aquatic habitats in various IDP camps were studied to compare the larval abundance of Cx. quinquefasciatus and An. gambiae s.l. The aquatic habitat dataset were overlaid onto Land Use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
31
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 29 publications
0
31
0
Order By: Relevance
“…People who settle in these densely populated peri-urban zones encounter communities already trying to overcome widespread poverty, as well as environmental degradation. These phenomena have resulted in overcrowding and increased densities of vectors due to excess land cover change (Jacob et al, 2003(Jacob et al, , 2006b(Jacob et al, , 2007(Jacob et al, , 2008d. Because the status and trends of land use and urbanization significantly impact vector mosquito habitat productivity, accurate, up-to-date, and spatiallyerror-free data of georeferenced spatiotemporal-sampled data are required to implement larval control strategies that target prolific habitats in SSA urban environments.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…People who settle in these densely populated peri-urban zones encounter communities already trying to overcome widespread poverty, as well as environmental degradation. These phenomena have resulted in overcrowding and increased densities of vectors due to excess land cover change (Jacob et al, 2003(Jacob et al, , 2006b(Jacob et al, , 2007(Jacob et al, , 2008d. Because the status and trends of land use and urbanization significantly impact vector mosquito habitat productivity, accurate, up-to-date, and spatiallyerror-free data of georeferenced spatiotemporal-sampled data are required to implement larval control strategies that target prolific habitats in SSA urban environments.…”
Section: Introductionmentioning
confidence: 98%
“…Densely packed housing in shantytowns and slums, inadequate drinking water supplies, excessive trash, and dysfunctional surface-water drainage systems in urban areas of Sub-Saharan Africa (SSA) have combined to create favorable habitats for the proliferation of vectors and reservoirs of communicable diseases Afrine et al, 2004;Mwangangi et al, 2007;Jacob et al, 2008d). As a consequence, vector-borne diseases such as malaria, lymphatic filariasis, and dengue fever are becoming major public health problems.…”
Section: Introductionmentioning
confidence: 98%
“…gambiae s.l. aquatic habitats, in urban environments, can be influenced by vector control activities host density (Snow et al 1998, Mutero et al 2000, Jacob et al 2005, 2008c, proximity to larval habitats and blood-meal hosts (Washino and Tempelis 1983, Minakawa et al 2002, quality of the larval habitats (Lyimo and Takken 1993, Gimnig et al 2002, Okech et al 2007), availability of domestic animals , Mwangangi et al 2007, Sota and Mogi 2008 and inter-human variation in mosquito preferences, based on host odours and other cues Knols 1999, Muturi et al 2007a). Studies have also shown that transitions in land use land cover (LULC) in urban areas can create variations in geographical locations of An.…”
Section: Introductionmentioning
confidence: 98%
“…gambiae s.l. aquatic habitats and their larval productivity (Khambea et al 1994, Chinery 1995, Jacob et al 2003, 2008c, Diuk-Wasser et al 2007). If spatial autocorrelation patterns remain present in an An.…”
Section: Introductionmentioning
confidence: 99%
“…The four possibilities of stereo image processing for DEM generation are Fore-Aft, Fore-Nadir, Aft-Nadir and Fore-Aft-Nadir images as a pair [19]. The simultaneous acquisition of along-track stereo data has a strong advantage in terms of radiometric variation versus the multi-date acquisition of across-track stereo data which has been traditionally employed in past research for identifying terrain-related explanatory covariates of floodwater mosquito habitats [20]. The across-track approach has been applied frequently since 1980, first with Landsat from two adjacent orbits, then with SPOT using across-track steering capabilities and finally with IRS-I C/D.…”
Section: Introductionmentioning
confidence: 99%